The Prognostic value of CA15-3, CA125, CEA in breast cancer patients undergoing chemotherapy: Prognostic value of CA15-3, CA125, CEA in breast cancer patients - Ge, Ying (Journal of Medical Biochemistry, 2025)
Objective To explore the prognostic value of cancer antigen 15-3 (CA15-3), Carbohydrate antigen 125 (CA125), Carcino-embryonic antigen (CEA) in breast cancer patients undergoing chemotherapy. Method The data of 100 patients with breast cancer who received chemotherapy in a hospital from May 2022 to May 2024 are selected. Patients are divided into a control group and test group based on different intervention methods and hospital stays. The control group receives routine nursing interventions. The test groupimplements exercise intervention under planned behavior planning, 50 cases in each group. The exercise cognitive score, cancer related fatigue, and serum tumor marker levels of patients are compared before, 2 weeks, and 4 weeks of intervention. Results Before intervention, they had no difference in exercise cognition scores, Cancer-Related Fatigue (CFS) scores, and serum tumor marker levels (P>0.05).After 2 and 4 weeks of intervention, the exercise attitude, exercise values, exercise behavior control, and exercise motivation in the testgroup exceeded the control group,(P<0.05).The scores of behavioral fatigue, sensory fatigue, emotional fatigue, and cognitive fatigue in the test group were below the control group, (P<0.05).The CA15-3, CA125, and CEA in the test group were below the control group, (P<0.05). Conclusion: Exercise intervention under planned behavior planning is conducive to improving the cognition of breast cancer chemotherapy patients on exercise knowledge, alleviating body fatigue, and reducing the serum markers.